New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species - Gilasian, Ebrahim; Vujić, Ante; Hauser, Martin; Parchami-Araghi, Mehrdad (Zootaxa, 2017)
The fauna of hoverflies of a variety of habitats from Iran was studied with different collecting methods including Malaise traps, from 2005-2015. Two new species, Pocota hyrcanica Gilasian & Hauser sp. nov. and Sphiximorpha ziegleri Gilasian & Vujić sp. nov., are described from Iran. Illustrations of the male genitalia and photographs of the new species are provided. Their morphological differences with similar species are stated. In addition, data on 14 hoverfly species new to Iran are provided, including the first records of five genera, Brachypalpus Macquart, Palumbia Rondani, Pocota Le Peletier & Serville, Pseudodoros Becker and Sphiximorpha Rondani. As a result of our study, the number of hoverfly species recorded from Iran rises to 222.